2015
DOI: 10.3109/23744235.2015.1028097
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of polymorphisms with significant resistance to NS5A inhibitors in treatment-naive patients with hepatitis C virus genotypes 1a and 3a in Sweden

Abstract: Using this method, baseline resistance can be examined and the data could have a potential role in selecting the optimal and cost-efficient treatment for the patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 27 publications
0
30
0
Order By: Relevance
“…In the United States, it has been described a prevalence ranging 9‐12% for G1a . In Europe, recent studies have reported rates of prevalence ranging from 1.6% in Sweden to 12.5% in Italy . In Spain, Calleja et al and Palladino et al described rates of prevalence around 6%.…”
Section: Discussionmentioning
confidence: 97%
“…In the United States, it has been described a prevalence ranging 9‐12% for G1a . In Europe, recent studies have reported rates of prevalence ranging from 1.6% in Sweden to 12.5% in Italy . In Spain, Calleja et al and Palladino et al described rates of prevalence around 6%.…”
Section: Discussionmentioning
confidence: 97%
“…With the exception of NS5B nucleoside analogues, the current DAAs target the NS3, as well as the allosteric sites of NS5B and NS5A, which all have a low threshold of resistance[10,18]. Data from both replicon analysis and from clinical trials have consistently identified viral mutations that can be associated with antiviral treatment failure[19].…”
Section: Discussionmentioning
confidence: 99%
“…Resistance to either drug correlated inversely with treatment success and compromised both. While baseline viral polymorphisms to many current DAAs have been well known, their clinical significance have often been unclear [Palanisamy et al, ; Lindström et al, ]. For example, global analyses of data from phase 3 trials of ledipasvir/sofosbuvir identified slight to substantial impact of baseline NS5A RAVs on SVR rate, with a greater impact from variants conferring a high degree of resistance in vitro [Afdhal et al, ,; Kowdley et al, ].…”
Section: Future Directionsmentioning
confidence: 99%